THE ROLE OF CORPORATE SOCIAL RESPONSIBILITY IN CONSUMPTION COMPANIES IN INDONESIA - Wastam Wahyu Hidayat (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This This study aims to determine whether there is an influence of firm size, profitability, and growth on corporate social responsibility in companies listed on the Indonesia Stock Exchange in 2018-2020. Variables used in this study are firm size, profitability, and growth as independent variables and corporate social responsibility as the dependent variable. The selection of samples in this study using purposive sampling method with the criteria that have been determined obtained 35 companies for 3 years so that the total sample used is 105 data. The type of data used is secondary data obtained from annual reports and sustainability reports. This hypothesis was tested using descriptive statistical analysis, classic assumption tests, multiple regression analysis, and hypothesis testing. The results showed that Firm Size partially had a negative and significant effect on Corporate Social Responsibility while Profitability and Growth had no effect on Corporate Social Responsibility and simultaneously Firm Size, Profitability, and Growth had no effect on Corporate Social Responsibility..